National Hockey League players' experiences with career-ending concussions. Issue 5 (11th March 2013) - Caron, Jeffrey G; Bloom, Gordon A; Johnston, Karen M; Sabiston, Catherine M
Abstract : Objective: This study investigated the experiences of National Hockey League (NHL) players who retired due to medically diagnosed concussions they incurred during their playing careers. Design: An Interpretative Phenomenological Analysis (IPA; Smith et al, 2009) was used to examine the interview data. IPA is a qualitative research methodology used to understand and explore how people make sense of important life experiences and has been commonly used in health research (Smith, 2011). Setting: Interviews were conducted in various cities in North America. Participants: Five former NHL players whose professional careers spanned more than 10 seasons were interviewed for this project. Results: Participants in this study articulated the type and intensity of the physical (eg, headaches, visual impairments) and psychological (eg, isolation, depression, suicidal ideation) concussion symptoms they endured during their careers, including how these symptoms impacted their professional careers, quality of lives, and relationships with family members and medical professionals. Participants said they continued to experience physical symptoms such as headaches, sensitivity to bright lights, and concentration problems after their careers, which has affected their post-athletic lives and has disturbed their daily functioning. Conclusions: These are the first results to empirically document the experiences of professional athletes who suffered career-ending concussions. Findings from this study concur with McCrory et al 's (2009) call for longitudinal research to better understand the implications of concussive injury. Additionally, our results indicate a need for psychological counselling in conjunction with medical guidance during rehabilitation from concussion and transition to post-athletic lives. Competing interests: None.